Risk factors for childhood overweight and obesity in Ukraine and Germany - Yakovenko, Vira; Bettendorf, Markus; Hoffmann, Georg F.; Grulich-Henn, Jürgen (Journal of clinical research in pediatric endocrinology, 2019)
Objective: The prevalence of overweight and obesity in childhood and adolescence are rapidly increasing and influenced by genetic, familial, environmental, socioeconomic and cultural factors. The aim of the study was to compare risk factors for childhood obesity in Ukraine (UA) and Germany (DE) using comparable investigative tools. - Methods: Two groups of children, aged 8 to 18 years, from DE (93 children) and UA (95 children) were divided into overweight and obese groups. Anthropometric data and detailed medical history were collected. - Results: Risk factors in pregnancy (prematurity, weight gain >20 kg, early contractions) were equally frequent in both groups. Positive correlations of body mass index (BMI)-standard deviation score (SDS) between children and mothers were noted. The proportion of family members with diabetes mellitus was lower in the UA group. Obesity was more frequent at one year of age in DE children. The DE group also became overweight at an earlier age and remained overweight over a longer period of time compared to UA. The mean BMI-SDS of obese children was lower in the UA group. In both groups waist circumference to height ratio was >0.5, indicating presence of a cardiometabolic risk factor. About half of the patients in both groups had blood pressure values exceeding the 95th percentile. - Conclusion: Similar risk factors for obesity were observed among two groups of children in UA and DE. Differences were observed regarding the prevalence of specific risk factors for childhood obesity. Population-specific distribution of risk factors needs to be considered in order to optimize prevention and treatment strategies.
Gesehen am 08.10.2019